2002
DOI: 10.1086/344213
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism, R653Q, in the Trifunctional Enzyme Methylenetetrahydrofolate Dehydrogenase/Methenyltetrahydrofolate Cyclohydrolase/Formyltetrahydrofolate Synthetase Is a Maternal Genetic Risk Factor for Neural Tube Defects: Report of the Birth Defects Research Group

Abstract: Women who take folic acid periconceptionally reduce their risk of having a child with a neural tube defect (NTD) by >50%. A variant form of methylenetetrahydrofolate reductase (MTHFR) (677C-->T) is a known risk factor for NTDs, but the prevalence of the risk genotype explains only a small portion of the protective effect of folic acid. This has prompted the search for additional NTD-associated variants in folate-metabolism enzymes. We have analyzed five potential single-nucleotide polymorphisms (SNPs) in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
187
4

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 217 publications
(209 citation statements)
references
References 37 publications
14
187
4
Order By: Relevance
“…29 With regard to the MTHFD1 polymorphism, its functional role in folate pool maintenance has been suggested: women with the MTHFD1 AA1958 genotype were found to be at an increased risk of having NTD-affected offspring. 18 In addition, the conservation of an arginine residue at the corresponding position of the MTHFD1 gene across numerous species suggests that replacement with glutamine, caused by a G to A base substitution, may have functional consequences. 18 Since MTHFD1 arg653gln replacement lies within the 10-formyl-THF synthase domain of MTHFD1, it is possible that a reduction in 10-formyl THF formation could shift folate balance towards 5,10-methylene-THF pools required for TS synthesis.…”
Section: Dfs But Not Os)mentioning
confidence: 99%
See 2 more Smart Citations
“…29 With regard to the MTHFD1 polymorphism, its functional role in folate pool maintenance has been suggested: women with the MTHFD1 AA1958 genotype were found to be at an increased risk of having NTD-affected offspring. 18 In addition, the conservation of an arginine residue at the corresponding position of the MTHFD1 gene across numerous species suggests that replacement with glutamine, caused by a G to A base substitution, may have functional consequences. 18 Since MTHFD1 arg653gln replacement lies within the 10-formyl-THF synthase domain of MTHFD1, it is possible that a reduction in 10-formyl THF formation could shift folate balance towards 5,10-methylene-THF pools required for TS synthesis.…”
Section: Dfs But Not Os)mentioning
confidence: 99%
“…18 In addition, the conservation of an arginine residue at the corresponding position of the MTHFD1 gene across numerous species suggests that replacement with glutamine, caused by a G to A base substitution, may have functional consequences. 18 Since MTHFD1 arg653gln replacement lies within the 10-formyl-THF synthase domain of MTHFD1, it is possible that a reduction in 10-formyl THF formation could shift folate balance towards 5,10-methylene-THF pools required for TS synthesis. In addition, genomic imbalance corresponding to the MTHFD1 locus was found in MTXresistant T-cell ALL cell lines.…”
Section: Dfs But Not Os)mentioning
confidence: 99%
See 1 more Smart Citation
“…The second change, a 1958G>A substitution polymorphism resulting in replacement of the arginine residue at position 653 by glutamine (R653Q), turned out to be present in both patients and controls with similar frequencies. More recently, Brody et al (2002) demonstrated that MTHFD1 1958G>A polymorphism is a maternal risk factor for NTD risk in the Irish population. Mothers who possess two copies of the MTHFD1 1958A allele have an increased risk of an NTD-affected pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers who possess two copies of the MTHFD1 1958A allele have an increased risk of an NTD-affected pregnancy. There was also a suggestion that the MTHFD1 1958A allele decreases fetal viability (Brody et al 2002).…”
Section: Introductionmentioning
confidence: 99%